2023
DOI: 10.1590/2447-536x.v29i2.2548
|View full text |Cite
|
Sign up to set email alerts
|

Muscari seed germination enhancement by using sulfuric acid, and stratification priming

Abstract: Muscari with absorbing color is a widespread and commercial species. As a pot and bedding bulb flower has excellent adaptability and vigorous growth in late winter and early spring. The quantity and uniformity of Muscari propagation by seed and the importance of seed priming will be measured in current experiment. The selected M. neglectum populations which already were gathered in our previews research and M. armeniacum were evaluated under separated sulfuric acid (5, 15, and 20 min) and hot water (5, 15, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The positive obtained effects of pre-germinative treatments are similar to those of Labbaf et al (2023) [20], who, by investigating the effects of sulfuric acid and stratification priming on seed germination, found a decrease in germination time to 15 days using a 5 min sulfuric acid treatment plus a 45-day stratification treatment.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The positive obtained effects of pre-germinative treatments are similar to those of Labbaf et al (2023) [20], who, by investigating the effects of sulfuric acid and stratification priming on seed germination, found a decrease in germination time to 15 days using a 5 min sulfuric acid treatment plus a 45-day stratification treatment.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of Muscari spp., Labbaf et al (2023) [20] studied how sulfuric acid and stratification treatments influence the germination of seeds. These authors indicated that only the combination of scarification treatment with sulfuric acid at 15 min and a 45day stratification period allowed for the germination of Muscari armeniacum, and sulfuric acid treatment at 5 min with a 45-day stratification period seeds resulted in a rapid and uniform germination of Muscari neglectum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, chemical scarification with H 2 SO 4 has been particularly effective in enhancing seed germination and seedling growth in various plant species. For instance, in okra [40,41], strelitzia [42], muscari [43], and raspberry seeds [44], H 2 SO 4 treatment has been found to break physical dormancy barriers and promote successful germination. Breaking physical dormancy can also take place as seeds pass through an animal's digestive system.…”
Section: Effect Of Seed Scarificationmentioning
confidence: 99%
“…The seeds of the genus Astragalus have seed dormancy due to the hard seed coat, but they have great potential to break this dormancy and these varies depending on many factors, including plant environments as well as depending on different plant species [5]. It is reported that acid treatment is considered an effective method of enhancing seed germination for plant species in which dormancy is caused by the hardness of the seed coat [6,7,8,9]. Treatment with growth and development hormone BAP with gibberellic acid can improve the germination of seeds and be better than treatment BAP with sulfuric acid on seed germination [10].…”
Section: Introductionmentioning
confidence: 99%